1990
DOI: 10.1080/03670244.1990.9991118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resettlement on nutritional status of mothers and children in lowland Papua new Guinea

Abstract: Nutritional status of three ethnic groups living at Gavien, a rubber resettlement project in lowland Papua New Guinea, was compared with that of people living in the home areas: Grass Country (hunter-gatherers); Wosera (agriculturalists); Middle Sepik (hunter-gatherers with limited agriculture).Anthropometry of mothers (n=115) and children (n=115) was completed during wet and dry seasons. Blood samples were collected to identify anemia and malarial infection.Grass Country children in Gavien were higher in weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Changes in nutritional status have (McNair and Learoyd, 1989), access to services, and/or participation in a cash economy (Bogan and Crittenden, 1987;Crittenden and Baines, 1985). Of these factors, income earning or participation in a cash economy at the household (Forsyth, 1982;Tracer et al, 1998), community (Bogan and Crittenden, 1987), and population levels (Shack et al, 1990a) have had a significant impact on the nutritional status of children in Papua New Guinea. With cash income there is a greater dependence on imported foods, resulting in improved protein and energy intakes and larger body size (Harvey and Heywood, 1983;Shack et al, 1990b;Tracer et al, 1998;Ulijaszek et al, 1987;Zemel and Jenkins, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in nutritional status have (McNair and Learoyd, 1989), access to services, and/or participation in a cash economy (Bogan and Crittenden, 1987;Crittenden and Baines, 1985). Of these factors, income earning or participation in a cash economy at the household (Forsyth, 1982;Tracer et al, 1998), community (Bogan and Crittenden, 1987), and population levels (Shack et al, 1990a) have had a significant impact on the nutritional status of children in Papua New Guinea. With cash income there is a greater dependence on imported foods, resulting in improved protein and energy intakes and larger body size (Harvey and Heywood, 1983;Shack et al, 1990b;Tracer et al, 1998;Ulijaszek et al, 1987;Zemel and Jenkins, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Papua New Guinea is experiencing rapid changes as a result of westernization and modernization (Ganguli, 1981). The impact of broad socioeconomic developments, particularly cash-cropping and wage labor, on the nutritional status of children and adults has been examined in various temporal, ecological, and geographical contexts (Norgan, 1995;Shack et al, 1990a;Ulijaszek et al, 1987Ulijaszek et al, , 1989. While there was some debate regarding the effects of cash-cropping on nutritional status in the late 1970s, more recent studies have demonstrated that socioeconomic changes, particularly in the highlands, are associated with larger body size (see Heywood and Hide, 1992).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the regression analysis, independent variables that were highly correlated with one another (r ^ 0.5) were identified and screened to avoid problems of multicollinearity. Independent variables utilized in the regressions are listed elsewhere (Shack et al, 1990). Because of the number of regressions involved, the results presented here will focus primarily on differences by "site".…”
Section: Methodsmentioning
confidence: 99%
“…A companion paper (Shack et al, 1990) describes anthropométrie and hematological data for the same groups of women and children.…”
Section: Introductionmentioning
confidence: 99%